The first World Health Organization International Standard for infliximab products: A step towards maintaining harmonized biological activity. Issue 1 (2nd January 2019) - Metcalfe, Clive; Dougall, Thomas; Bird, Chris; Rigsby, Peter; Behr-Gross, Marie-Emmanuelle; Wadhwa, Meenu; study, participants of the
ABSTRACT: Due to the increase in the number of infliximab products, the need for global harmonization of the bioactivity of this monoclonal antibody was recognized by the World Health Organization (WHO). In response, the National Institute for Biological Standards and Control (NIBSC) developed the first international standard (IS) for infliximab, which targets tumour necrosis factor (TNF). Each ampoule is assigned values of 500 IU of TNF neutralizing activity and 500 IU of binding activity. Two preparations of infliximab were formulated and lyophilized at NIBSC prior to evaluation in a collaborative study for their suitability to serve as an IS for the in vitro biological activity of infliximab. The study involved participants using in vitro cell-based bioassays (TNF neutralization, antibody-dependent cell-mediated cytotoxicity and complement-dependent cytotoxicity) and binding assays. The results of this study showed that the candidate preparation, coded 16/170, is suitable as an IS for infliximab bioactivity. This infliximab IS from NIBSC, is intended to support in vitro bioassay calibration and validation by defining international units of bioactivity. The proposed unitages, however, are not intended to revise product labelling or dosing requirements, as any decisions regarding this relies solely with the regulatory authorities. Furthermore, the infliximab IS is not intended for determining the specific activity of products, nor to serve any regulatory role in defining biosimilarity. We briefly discuss the future use of WHO international standards in supporting the global harmonisation of biosimilar infliximab products.